2018
DOI: 10.1111/cmi.12833
|View full text |Cite
|
Sign up to set email alerts
|

NK cells inhibit anti-Mycobacterium bovisBCG T cell responses and aggravate pulmonary inflammation in a direct lung infection mouse model

Abstract: Tuberculosis remains a threat to public health. The major problem for curing this disease is latent infection, of which the underlying mechanisms are still not fully understood. Previous studies indicate that natural killer (NK) cells do not play a role in inhibiting the growth of Mycobacterium tuberculosis in the lung, and recent studies have revealed that NK cells regulate the adaptive immunity during mycobacterial infection. By using a mouse model of direct lung infection with Mycobacterium bovis bacillus C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Bacillus Calmette-Guérin-infected macrophages up-regulated NKG2D ligands, which induced their lysis via this receptor-ligand interaction. Finally, the blocking of NKG2D with a monoclonal antibody restored the survival of the macrophages and the T cell-mediated immune response (89).…”
Section: Mycobacterium Tuberculosis and Other Mycobacteriamentioning
confidence: 97%
See 2 more Smart Citations
“…Bacillus Calmette-Guérin-infected macrophages up-regulated NKG2D ligands, which induced their lysis via this receptor-ligand interaction. Finally, the blocking of NKG2D with a monoclonal antibody restored the survival of the macrophages and the T cell-mediated immune response (89).…”
Section: Mycobacterium Tuberculosis and Other Mycobacteriamentioning
confidence: 97%
“…Some studies were also performed on Mycobacterium bovis Bacillus Calmette-Guérin (BCG), an attenuated mycobacterial strain used as an anti-tuberculous vaccine ( 89 ). For example, it was demonstrated in vitro that CD56 bright NK cells reacted to this microorganism by proliferation and IFN-γ production, whereas their CD56 dim counterparts better up-regulated the cytolytic proteins perforin and granzyme A ( 90 ), all of which was largely expected based on what is known about the functional specialization of these two NK cell subsets ( 1 3 ).…”
Section: Gram-positive Bacteriamentioning
confidence: 99%
See 1 more Smart Citation
“…Tu et al., expanded Vδ2 cells in vitro with the NBP pamidronate (PAM) and injected them into influenza infected humanized mice, demonstrating an improvement in disease severity and control of viral replication ( 110 ). Studies have also shown the NKG2D ligand MICA to be upregulated on epithelial and DCs after M. tb in humans ( 111 ), and mice NKG2D ligands Rae-2 and MULT1 are upregulated after BCG infection in the murine model ( 112 ).…”
Section: Bcg Stimulation Of γδ T Cells To Combat Non-tuberculosis Diseasesmentioning
confidence: 99%
“…In addition to inflammation, blast exposure also induced oxidative stress [6, 7] and apoptosis [8] in the lungs of experimental animals. Recent studies reported that T cell activation had a pivotal role in the development of inflammation [9, 10]. At least two signals are required for the full activation of T cells.…”
Section: Introductionmentioning
confidence: 99%